2016
DOI: 10.1002/admi.201600222
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Surface Electrochemistry by Strained Epitaxial Pt Thin Film Model Electrodes Prepared by Pulsed Laser Deposition

Abstract: toward different reactions such as methanol [ 1 ] or ethanol [ 2,3 ] oxidation, hydrogen oxidation, [ 4 ] and oxygen reduction reaction. [ 5,6 ] However, the slow kinetics of some of these reactions results in great losses concerning the respective energy conversion effi ciencies. This drawback, together with Pt dissolution phenomena requires a large amount of Pt at the electrode. The accompanying cost and scarcity of Pt represent the prime impediments toward a broad practical application of fuel cells. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Morimoto and co-workers showed that atomic layer deposition (ALD) can be successfully employed to produce Pt electrodes on SiO2 substrates for testing on MEAs [56]. More recently, Schmidt and co-workers investigated the influence of the growth mechanism on the surface structure of thin films fabricated by pulsed laser deposition (PLD), demonstrating that strain can enhance the ORR activity [57,58]. Kim and co-workers fabricated nanoparticulate thin films of alloys of Pt-late transition metals together with Pt-Y and Pt-La for ORR using magnetron sputtering [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Morimoto and co-workers showed that atomic layer deposition (ALD) can be successfully employed to produce Pt electrodes on SiO2 substrates for testing on MEAs [56]. More recently, Schmidt and co-workers investigated the influence of the growth mechanism on the surface structure of thin films fabricated by pulsed laser deposition (PLD), demonstrating that strain can enhance the ORR activity [57,58]. Kim and co-workers fabricated nanoparticulate thin films of alloys of Pt-late transition metals together with Pt-Y and Pt-La for ORR using magnetron sputtering [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…They observed a strain effect on the adsorption of OH – species and the oxidation of CO ads . Similarly, model Pt thin film electrodes were prepared by Temmel et al using a pulsed laser deposition (PLD) method to investigate CO oxidation on strained Pt surfaces. Single-crystal (100)- and (111)-oriented strontium titanate (STO) substrates were used for epitaxial deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The optimized hierarchical oxygen-incorporated amorphous MoS x electrocatalyst delivered extremely small overpotentials (170 mV at À100 mA cm À2 ), superb kinetics Apart from these common laser-induced syntheses of electrocatalysts, atomic epitaxial growth on an appropriate substrate has also been designed and developed. 175,176 Chung's group reported the influence of both tensile and compressive strains on the generation behaviors of Ruddlesden-Popper (RP) two-dimensional planar faults in (001) epitaxial LaNiO 3 thin films by using two distinct substrates of LaAlO 3 and SrTiO 3 , as illustrated in Figure 11(F,G). 177 The number of RP faults for SrTiO 3 substrate is about a two times higher than that for the case using the LaAlO 3 , indicating that the RP-fault formation can be improved for the LaNiO 3 film under a tensile strain field.…”
Section: Electrocatalysismentioning
confidence: 99%